2020
DOI: 10.1590/scielopreprints.1241
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factores Asociados a Mortalidad en Pacientes Hospitalizados Con Covid-19: Cohorte Prospectiva en El Hospital Nacional Edgardo Rebagliati Martins. Lima, Perú

Abstract: Objetivos. Determinar los factores asociados a mortalidad de los pacientes adultos hospitalizados con COVID-19 en un hospital de referencia de la seguridad social. Materiales y métodos. Se realizó un estudio de cohorte prospectivo. Se incluyó a pacientes mayores de 18 años hospitalizados con el diagnostico de infección por SARS-CoV-2 y se excluyó a quienes ingresaron asintomáticos respiratorios, con prueba rápida serológica positiva al ingreso y sin imágenes compatibles. Los datos se recolectaron a partir de l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
3
1
19

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 0 publications
4
3
1
19
Order By: Relevance
“…Regarding laboratory markers, there are reports of the relationship between increased leukocytes, CRP, LDH, ferritin, D-dimer and decreased lymphocytes with mortality, data that relate the exaggerated inflammatory response in patients with Covid-19 with increased mortality, such findings are congruent with our findings [30][31][32][33] , in relation to the gasometrical characteristics it is described that SatO2<90% persistent despite increased oxygen support, pO2 < 68 mmHg and decreased pO2/FiO2 are related to higher mortality in the context of the severity of respiratory compromise 34 , in this series it was found that most patients needed oxygen support and showed a significantly decreased PaO2/FiO2.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Regarding laboratory markers, there are reports of the relationship between increased leukocytes, CRP, LDH, ferritin, D-dimer and decreased lymphocytes with mortality, data that relate the exaggerated inflammatory response in patients with Covid-19 with increased mortality, such findings are congruent with our findings [30][31][32][33] , in relation to the gasometrical characteristics it is described that SatO2<90% persistent despite increased oxygen support, pO2 < 68 mmHg and decreased pO2/FiO2 are related to higher mortality in the context of the severity of respiratory compromise 34 , in this series it was found that most patients needed oxygen support and showed a significantly decreased PaO2/FiO2.…”
Section: Discussionsupporting
confidence: 92%
“…Mortality in CKD secondary to pulmonary infections in general is 51.9% and this varies according to increasing age 18,24,27-30 , there is evidence of reports such as that of Yang et al 19 on mortality in CKD infected by COVID19 which ranges between 6% and 22.7%; also in Perú a study reports up to 46% mortality 31 ; in our research a mortality of 20% was obtained, which correlates with the aforementioned.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Age was associated with higher mortality, in our series, the highest proportion of deaths were in the age groups over 60 years, besides, that for every 10 years that the age increased, the risk of dying increased by 32%, This was described in [15], a large series of Chinese population data, in which the age groups 60 to 69, 70 to 79 and over 80 years had 3.6%, 8%, and 14.8% mortality respectively.…”
Section: Discussionsupporting
confidence: 67%
“…In conclusion, the largest series of patients hospitalized with COVID-19 in the country was reported; the population tested presented high mortality and was associated with age, comorbidities, [16] inflammatory markers, and respiratory involvement. These results could serve us to propose strategies for reorganizing the care system and to direct management differentiating in [15] patients with higher risk factors for mortality.…”
Section: Discussionmentioning
confidence: 98%